Al-NaOH-Composited Liquid Metal: A Fast-Response Water-Triggered Material with Thermal and Pneumatic Properties. (December 2020) - Yuan, Bo; Sun, Xuyang; Liu, Jing
Abstract: Water-triggered materials are receiving increasing attentions due to their diverse capabilities such as easy operation, soft actuation, low cost, environmental friendliness, and many more other advantages. However, most of such materials generally have a long reaction time and require strict preservation conditions, which limit their adaptability in practice. In this study, a novel water-triggered material based on Al-NaOH-composited eutectic gallium–indium (eGaIn) alloys was proposed and demonstrated, which is rather fast-responsive and deformable. Once water is applied, the material thus fabricated would achieve a temperature rise of 40 °C in just several seconds along with gas production, indicating its big potential to be used as a thermal and pneumatic actuator. Further, the new material's reusability and degradation ability were also tested. Following that, a double-layer-structure smart bandage was designed, whose bulk was filled with Al-NaOH-composited eGaIn while BiInSn served as outer supporting material. According to the experiments, a sheet structure with a thickness of 2 mm would support a weight of 1.8 kg after it was subjected to a cooling process, which is much better than the weight-bearing capability of fiberglass. In addition, a prototype of a water-triggered sphere robot was also fabricated using Al-NaOH-eGaIn, which realized rolling and bouncing behaviors under specific external stimulation. These findings indicate the potential value of the present material in developing future wearable devices, soft actuators, and soft robotics.